2005
DOI: 10.1210/en.2004-1322
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 Modulates Expression of Chemokines and Cytokines in Pancreatic Islets: Implications for Prevention of Diabetes in Nonobese Diabetic Mice

Abstract: 1,25-Dihydroxyvitamin D(3) (1,25-(OH)(2)D(3)) is an immune modulator that prevents experimental autoimmune diseases. Receptors for 1,25-(OH)(2)D(3) are present in pancreatic beta-cells, the target of an autoimmune assault in nonobese diabetic (NOD) mice. The aim of this study was to investigate the in vivo and in vitro effects of 1,25-(OH)(2)D(3) on beta-cell gene expression and death and correlate these findings to in vivo diabetes development in NOD mice. When female NOD mice were treated with 1,25-(OH)(2)D(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(145 citation statements)
references
References 49 publications
5
129
0
6
Order By: Relevance
“…Multiple mechanisms contribute to induction of DC tolerogenicity by VDR agonists, from down-regulation of costimulatory molecules, both membrane-bound as CD40, CD80, CD86 and secreted as IL-12, to up-regulation of anti-inflammatory molecules like 25). Additional mechanisms involve modulation of chemokine secretion, enhancing the production of chemokines able to recruit regulatory/suppressor T cells, and inhibiting chemokine production by target organs in autoimmune diseases (26,27). These effects are not limited to in vitro activity: 1,25(OH) 2 D 3 and its analogs can also induce DCs with tolerogenic properties in vivo, as demonstrated in models of allograft rejection (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms contribute to induction of DC tolerogenicity by VDR agonists, from down-regulation of costimulatory molecules, both membrane-bound as CD40, CD80, CD86 and secreted as IL-12, to up-regulation of anti-inflammatory molecules like 25). Additional mechanisms involve modulation of chemokine secretion, enhancing the production of chemokines able to recruit regulatory/suppressor T cells, and inhibiting chemokine production by target organs in autoimmune diseases (26,27). These effects are not limited to in vitro activity: 1,25(OH) 2 D 3 and its analogs can also induce DCs with tolerogenic properties in vivo, as demonstrated in models of allograft rejection (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that 1,25(OH) 2 D 3 induced and maintained high levels of A20, an anti-apoptotic protein, in rat RINm5F cells and human islets after exposure to inflammatory cytokines [86]. We recently performed a comparative study of different cell systems (whole rat islets, FACS-purified beta cells and INS-1E cells) and did not observe direct protection by 1,25(OH) 2 D 3 against cytokine-induced beta cell death, but demonstrated decreased expression of chemokines by beta cells treated with 1,25(OH) 2 D 3 [87].…”
Section: Vitamin D and Type 1 Diabetesmentioning
confidence: 99%
“…4,5 A role for vitamin D 3 in immune regulation has been demonstrated both in vivo and in vitro; 1,25(OH) 2 D 3 influences the growth, differentiation and cytokine production of various immune cells. [6][7][8] As a result, 1,25(OH) 2 D 3 has been proposed as a potential immunomodulatory agent in autoimmune diseases such as insulin-dependent diabetes mellitus, multiple sclerosis, inflammatory bowel disease and rheumatoid arthritis, [9][10][11] as well as in cancer 12 and infectious diseases such as HIV infection. 13 Regulatory T (Treg) cells are characterized by a CD4 + CD25 high phenotype and signature transcription factor, forkhead box protein 3 (Foxp3).…”
Section: Introductionmentioning
confidence: 99%